Entre a cópia, a importação e a originalidade: artes (e arquitetura) na década de 20, por intermédio das crônicas de Menotti del Picchia (1892-1977) e Mario de Andrade (1893-1945) - Castro, Ana Claudia Veiga de (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2005)
The paper focuses on the work of two modernist writers, Menotti del Picchia and Mario de Andrade, whose texts were published in the 1920s in Correio Paulistano and Diário Nacional, newspapers of Sao Paulo's Republican Party and the Democratic Party, respectively. The aim of the project is to shed some light on two particular periods of these authors' works - the beginning and the end of that decade. Matters of interest addressed in such writing include the quest for a national style in the arts and architecture during a decade characterized by intense urban and social changes, crises within the oligarchy that dominated Brazil's Old Republic and an ideological awakening that followed World War I, emphasizing the relationship of the authors and the coffee oligarchy.